Analisis Implementasi Pengelolaan Keuangan Desa dalam Alokasi Dana Desa (ADD) Desa Suka Jadi Kecamata Hinai Kabupaten Langkat Tahun 2023 - Ummi Kalsum; Aulia Aulia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to describe and analyze village financial management in the management of Village Fund Allocation in Suka Jadi. The research method used in this study is a qualitative approach with data collection techniques through observation, interviews and documentation. The informants in this study are all Suka So Village Apparatus in 2023 as many as 20 people. The results of the study show that the management of village finances, in this case the Village Fund Allocation (ADD) of Suka Jadi, is the village. The implementation of ADD disbursement in 2023 will be carried out in two stages, the first disbursement will only be partial, namely 60% of the ADD, and the rest will be released in the second stage, which is 40%. The first phase of disbursement of funds will only be realized in January 2023 and the second phase will be realized in July 2023. Meanwhile, the village apparatus honorarium is a routine expense that is paid every month. In the planning stage, procedurally it is in accordance with the regulations, but the target time is not in accordance with the regulations. In the implementation stage, procedurally it is in accordance with regulations even though there is a delay in the disbursement of funds. In the administration stage, it can be said that it is in accordance with the rules. The reporting stage can be said to be on time and in accordance with regulations